2022
DOI: 10.1093/scan/nsac003
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of negative emotion processing in subthreshold depression

Abstract: Subthreshold depression (SD) is regarded as a major risk factor for major depression. However, little is known about the neural mechanism of negative emotion processing in SD. The study aimed to examine the differentiate neural correlates for negative emotion processing in SD and health controls (HC) and to investigate changes in functional connectivity in SD compared with HC. BOLD responses of SD and HC were captured while performing a passive viewing task, which comprised a negative condition and a masked co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…A recent rs-fMRI study showed reduced FC between the VTA and SFG and supplementary motor area in MDD (Nakamura et al, 2020). Our previous task-based fMRI study found reduced SFG and middle frontal gyrus activations during negative emotion processing in adolescents with subthreshold depression (Zhang et al, 2022). Moreover, deep brain stimulation to the VTA and the medial forebrain bundle can improve the depressive symptoms in treatment-resistant MDD.…”
Section: Discussionmentioning
confidence: 96%
“…A recent rs-fMRI study showed reduced FC between the VTA and SFG and supplementary motor area in MDD (Nakamura et al, 2020). Our previous task-based fMRI study found reduced SFG and middle frontal gyrus activations during negative emotion processing in adolescents with subthreshold depression (Zhang et al, 2022). Moreover, deep brain stimulation to the VTA and the medial forebrain bundle can improve the depressive symptoms in treatment-resistant MDD.…”
Section: Discussionmentioning
confidence: 96%
“…MFG is a part of the dorsolateral prefrontal cortex, which is involved in cognitive control and emotion processing ( 96 ). Zhang et al ( 97 ) found that the MFG was responsible for aberrant negative emotion processing. The precentral gyrus is a crucial part of dorsal medial prefrontal cortex (dmPFC), which plays a critical role in the regulation of social cognition ( 98 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Beck Depression Inventory (BDI) (59) has been employed to measure the depressive level (60)(61)(62)(63)(64). Two depressive states were identified with the most commonly used cutoff BDI = 14 (BDI < 14, without depression; BDI ≥ 14, with depression) (65).…”
Section: Behavioral Data Acquisitionmentioning
confidence: 99%